Orbital motion and epicyclic oscillations around a black hole with magnetic charge - Mustafa, G.; Channuie, Phongpichit; Javed, Faisal; Bouzenada, Abdelmalek; Maurya, S. K.; Cilli, Arzu; Gudekli, Ertan (ELSEVIER, 2025)
This paper studies the orbital and epicyclic movements of test particles orbiting a black hole with magnetic charge but no rotation. We generate analytical solutions to explain the radial distributions of particular energy, and angular momentum, for steady circular orbits on the equatorial plane. By utilizing the effective potential technique, we evaluate the stability of these trajectories and the forces that influence particles within the magnetically charged black hole. Our results show how magnetic charge affects the innermost stable circular orbits. Additionally, we calculate the frequencies of radial and latitudinal harmonic oscillations using the parameters of the black hole, taking into account observers who are both nearby and far away. The research involves examining quasi-periodic oscillations around stable equatorial orbits, the precession of the periastron, and assessing particle collisions with a focus on the center of mass energy of the colliding particles.
Keywords: Black holes; Circular orbits; Particle dynamics; Epicyclic oscillations; QUASI-PERIODIC OSCILLATIONS; TELESCOPE RESULTS. I.; THIN ACCRETION DISKS; PARTICLE MOTION; SHADOW; GRAVITY; PARAMETERS; ORIGIN; MASS; Astronomy & Astrophysics